Bioefficacy of selected insecticides on late stage instars of bagworm, metisa plana (walker) / Mohammad Daniel Mat …[et al.] - Mat, Mohammad Daniel; Md Latip, Siti Noor Hajjar; Che Manan, Che Ahmad Hafiz; Che Razali, Ayman (Universiti Teknologi MARA Shah Alam, 2020)
Metisa plana is a significant oil palm pest in South East Asia and are well recognized for its devastating impact on oil palms in Malaysia. Due to the high intensity of the M. plana assault on oil palm plantation in the peninsular, Malaysia. The use of insecticides has become a famous means of controlling M. plana infestation when the economic threshold is reached. Three selected insecticides are Cypermethrin, Flubendiamide, and Bacillus thuringiensis tested for their toxicity toward M. plana. Late-stage instar of M. plana was collected at Felda Serting Hilir 4, Bahau, to be tested on three different pesticides, including one control treatment. For each treatment, five replications were exposed to the selected chemical by using the leaf dip bioassay method. The mortality of M. plana was recorded for eight consecutive days. Results showed that both Cypermethrin and Flubendiamide could achieve a 100% mortality rate within four days while it takes eight days for Bacillus thuringiensis and control treatment. Further study should be done in the field to obtain more accurate results when exposed to natural conditions and the environment